Manual comparativo de hidrología básica para drenaje superficial (2015)
The following degree project is aimed at presenting a simple and clear manual comparative of basic hydrology for surface drainage that through a bibliographic compilation and the development of examples, allows to analyze and compare different methodologies to perform a hydrological study related to surface drainage , emphasizing, mainly, in comparing traditional methodologies with systematized ones thanks to new computational tools. Although currently there are different easily accessible documents that are very useful at the time of carrying out surface drainage hydrological studies, the information systems and computer programs have systematized the methodologies that facilitate the elaboration of them. The aspects that are considered for the elaboration of a hydrological study can be analyzed in different ways, depending on the available information (hydroclimatology, cartography, satellite images, topography, land use, vegetation cover) of the study area and the region of the country. Nowadays, due to the development of computational tools, traditional methodologies are not used so frequently and often the results obtained with the methodologies that have arisen may not be so true, so the criteria and experience are necessary to determine if the results obtained are representative of the area being studied. Based on the above, it is intended to analyze the main traditional methodologies and the recently developed methodologies, in order to compare the results obtained when using them in real cases. This document, besides being a bibliographic compilation, is a compendium of the experiences acquired by the authors during their last work stage, having as main base the knowledge received in the chairs of computational hydrology and applied basic hydrology within the regular postgraduate program and the application and use of these in different projects in which he has been participating. One of the objectives sought is to leave these experiences reflected in an academic way, to be used and / or consulted by engineers interested in this type of topic.